EDANSA-2019: The Ecoacoustic Dataset from Arctic North Slope Alaska - Çoban, Enis Berk; Perra, Megan; Pir, Dara; Mandel, Michael (Zenodo, 2022)
We are sharing the Ecoacoustic Dataset from Arctic North Slope Alaska (EDANSA-2019), a dataset with audio samples collected from the area of 9000 square miles throughout the 2019 summer season on the North Slope of Alaska and neighboring regions. There are over 27 hours of labeled data according to 28 tags with enough instances of 9 important environmental classes to train baseline convolutional recognizers. Please see the following GitHub page for the accompanying publication, updates about the dataset, and baseline code: https://github.com/speechLabBcCuny/EDANSA-2019